Psychometric properties of “Hopefulness Scale for Adolescents” (HSA) - Rassouli, M; Gharebagh, Z; Safavi, M; Haghani, H (Advances in Nursing & Midwifery, 2010)
Background and Aim The concept of hopefulness in adolescents and its role in the health of this group are very important. Therefore, a valid and reliable tool to measure this concept is essential. This methodological study was performed to identify psychometric properties (validity and reliability) of “Hopefulness Scale for Adolescents” (HSA) in high school students of Tehran. Materials and Methods In this methodological research, 1918 girl and boy students from districts 3, 5, 9, 10 and 18 of Education Organization in Tehran were selected by random cluster sampling method. The subjects were asked to complete the scale along with a demographic questionnaire and Self-efficacy scale of Sherer et al. as a criterion scale. Construct and criterion validities were identified for the validity of the scale and internal consistencies as well as test-retest were measured for its reliability. Data were analyzed by calculation of factor analysis, coefficients of correlation and Cronbach’s alpha. Findings Construct validity was measured by exploratory factor analysis and revealed 2 factors, namely, optimistic and pessimistic thinking toward future. Coefficient correlation (r) of scores between the scale and Self-efficacy scale of Sherer et al. was 0.588 (P<0.001). Cronbach’s alpha and correlation (r) of scale scores in 2 times were 0.834 and 0.445 respectively. Conclusion Hopefulness Scale for Adolescents has satisfactory validity and reliability and can be used to measure hopefulness in this group. Keywords: Psychometric evaluation, Scale, Validity, Reliability, Hopefulness Scale for Adolescents (HSA). *Corresponding Author: Dr. Maryam Rassouli, Dept. of Pediatrics, Faculty of Nursing and Midwifery, Shahid Beheshti. University of Medical Sciences, Tehran, Iran. E-mail: rassouli.m@gmail.com